2008
DOI: 10.1111/j.1095-8312.2007.00907.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny and diversification history of Prosopis (Fabaceae: Mimosoideae)

Abstract: The genus Prosopis is an important member of arid and semiarid environments around the world. To study Prosopis diversification and evolution, a combined approach including molecular phylogeny, molecular dating, and character optimization analysis was applied. Phylogenetic relationships were inferred from five different molecular markers (matK-trnK, trnL-trnF, trnS-psbC, G3pdh, NIA). Taxon sampling involved a total of 30 Prosopis species that represented all Sections and Series and the complete geographical ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
66
2
11

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 56 publications
12
66
2
11
Order By: Relevance
“…While we currently lack data on the aloes, stonecrops, and asclepiads, every arid-adapted succulent lineage investigated thus far has followed a similar tempo of evolution: Although the origins of a pronounced succulent syndrome in these groups vary widely between ≈40 and 10 Ma, they all share a single timeframe of extensive global diversification in the late Miocene-Pliocene. Studies of other desert (nonsucculent) plants from various regions have also demonstrated a similar pattern of recent radiation (17)(18)(19)(20). The simultaneous diversification of arid-adapted lineages provides a general insight into the history of the world's arid regions, which has been limited by a bias against fossil formation in dry environments.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…While we currently lack data on the aloes, stonecrops, and asclepiads, every arid-adapted succulent lineage investigated thus far has followed a similar tempo of evolution: Although the origins of a pronounced succulent syndrome in these groups vary widely between ≈40 and 10 Ma, they all share a single timeframe of extensive global diversification in the late Miocene-Pliocene. Studies of other desert (nonsucculent) plants from various regions have also demonstrated a similar pattern of recent radiation (17)(18)(19)(20). The simultaneous diversification of arid-adapted lineages provides a general insight into the history of the world's arid regions, which has been limited by a bias against fossil formation in dry environments.…”
Section: Discussionmentioning
confidence: 85%
“…14). Blue line reflects decline in relative global temperatures, inferred from deep sea 18 O, which is primarily a metric of deep sea temperature and sea-ice volume. Gray area in background represents reconstructed atmospheric CO 2 levels and their uncertainty through time, collated from multiple proxies (27).…”
Section: Discussionmentioning
confidence: 99%
“…Chilensia (Tropaeolaceae) (see references in Luebert, 2011). However, only few of them have been dated at the crown node of that relationship: Bomarea (∼5 Ma; Chacón et al, 2012), Asteriscium and Eremocharis (both ∼11 Ma; Nicolas and Plunkett, 2014), Oxalis (∼20 Ma; Heibl and Renner, 2012), Prosopis (∼1 Ma; Catalano et al, 2008), Solanum sect. Lycopersicon (∼2 Ma; Särkinen et al, 2013), Vasconcellea (∼10 Ma; Antunes Carvalho and Renner, 2012), Alstroemeria (∼18 Ma; Chacón et al, 2012), Chaetanthera (∼10 Ma; Hershkovitz et al, 2006), Schizanthus (∼24 Ma; Särkinen et al, 2013).…”
Section: Biogeographical Relationships Of the Andean Floramentioning
confidence: 99%
“…Despite these advances, many cases of non-monophyletic genera revealed in recent phylogenies remain to be fully resolved. There is evidence to suggest that several important genera are, or may be, non-monophyletic, in particular Piptadenia (Jobson & Luckow, 2007), Prosopis (Catalano & al., 2008); Albizia Durazz and Archidendron F. Muell. (Brown & al., 2008 and unpub.…”
Section: Mimosoideaementioning
confidence: 99%
“…Recent phylogenetic studies of genera include Hoffmannseggia (Simpson & Ulibarri, 2006); Phaseolus (DelgadoSalinas & al., 2006); Paloue and related genera (Redden & Herendeen, 2006); Phyllolobium Fisch. (Zhang & Podlech, 2006); Lotus L. (Degtjareva & al., 2006(Degtjareva & al., , 2008; Piptadenia (Jobson & Luckow, 2007); Prosopis (Burghardt & Espert, 2007;Catalano & al., 2008); Paraserianthes I.C. Nielsen ; Platymiscium Vogel (Saslis- Lagoudakis & al., 2008); Mimosa (Bessega & al., 2008;Simon & al., 2011;Bessega & Fortunato, 2011); Bauhinia s.l.…”
Section: Integrating Morphologymentioning
confidence: 99%